Can Nonexperimental Methods Provide Unbiased Estimates of a Breastfeeding Intervention? A Within-Study Comparison of Peer Counseling in Oregon. (June 2019) - Altindag, Onur; Joyce, Theodore J.; Reeder, Julie A.
Between July 2005 and July 2007, the Oregon Supplemental Nutrition Program for Women, Infants and Children program conducted the largest randomized field experiment (RFE) ever in the United States to assess the effectiveness of a low-cost peer counseling intervention to promote exclusive breastfeeding. We undertook a within-study comparison of the intervention using unique administrative data between July 2005 and July 2010. We found no difference between experimental and nonexperimental estimates but failed to determine correspondence based on more stringent criteria. We show that tests for nonconsent bias in the benchmark RFE might provide an important signal as to confounding in the nonexperimental estimates.